Effect of subchronic in vivo exposure to nitrogen dioxide on lung tissue inflammation, airway microvascular leakage, and in vitro bronchial muscle responsiveness in rats. Issue 6 (June 1996) - Chitano, P; Rado, V; Di Stefano, A; Papi, A; Boniotti, A; Zancuoghi, G; Boschetto, P; Romano, M; Salmona, M; Ciaccia, A; Fabbri, L M; Mapp, C E
Abstract : OBJECTIVES: In a previous study on bronchoalveolar lavage fluid from rats exposed in vivo for seven days to 10 ppm nitrogen dioxide (NO2), it has been shown that there is an influx of macrophages into the airways. The present study investigated the effect of seven day exposure to 10 ppm NO2, on: (a) lung tissue inflammation and morphology; (b) airway microvascular leakage; (c) in vitro contractile response of main bronchi. METHODS: Lung tissue was studied by light microscopy, after fixing the lungs by inflation with 4% formalin at a pressure of 20 cm H2O. Microvascular leakage was measured by extravasation of Evans blue dye in the larynx, trachea, main bronchi, and intrapulmonary airways. Smooth muscle responsiveness was evaluated by concentration-responses curves to acetylcholine (10(-9)-10(-3) M), serotonin (10(-9)-10(-4) M), and voltage-response curves (12-28 V) to electrical field stimulation. RESULTS: Histology showed an increased total inflammation at the level of respiratory bronchioles and alveoli. No influx of inflammatory cells was found in the main bronchi. A loss of cilia in the epithelium of small airways and ectasia of alveolar capillaries was also found. By contrast, no alterations to microvascular permeability or modification of bronchial smooth muscle responsiveness was found. CONCLUSIONS: Subchronic exposure to 10 ppm NO2 causes airway inflammation and structural damage, but does not cause any persistent alteration to microvascular permeability or bronchial smooth muscle responsiveness in rats.